Plasma Pharmacokinetics of Ceftolozane/Tazobactam in Pediatric Subjects with Cystic Fibrosis. (4th October 2017) - Larson, Kajal; Bradley, John S; Arrieta, Antonio; Yang, Shan; Yu, Brian; Johnson, Matthew G; Rizk, Matthew; Rhee, Elizabeth
Abstract: Background: Ceftolozane/tazobactam (TOL/TAZ), a novel anti-pseudomonal cephalosporin/β-lactamase inhibitor combination, is approved for the treatment of complicated intra-abdominal infections (cIAI) and urinary tract infections (cUTI) in adults. TOL/TAZ has potent activity against Gram-negative pathogens associated with pulmonary infections in cystic fibrosis (CF). Limited data exists on the pharmacokinetics (PK) of TOL/TAZ in the CF population. The aim of this analysis is to evaluate plasma PK parameters in CF and non-CF pediatric subjects to assess whether CF alters the PK of TOL/TAZ. Methods: Nine subjects with CF were enrolled in the 2 to <18 y old cohort of an ongoing Phase 1 PK study of a single dose of intravenous TOL/TAZ in pediatric subjects with suspected or proven Gram-negative infection (NCT02266706). Population PK models for TOL and TAZ were developed using PK data from 12 adult studies and preliminary PK data from pediatric subjects. An exploratory analysis comparing model-derived plasma TOL and TAZ PK parameters between CF ( N = 9) and non-CF ( N = 9) pediatric subjects was conducted. Results: Mean (range) age and weight of the 9 CF subjects were 11.4 y (5.5–17.5 y) and 37.4 kg (17.4–60 kg), respectively. For TOL, the mean (SD) systemic clearance (CL) normalized by weight was 0.16 (0.03) and 0.15 (0.03) L/hours/kg in CF and non-CF subjects, respectively, suggesting no difference in CL; similar observations were made for volume of the central compartment normalized by weight. All subjects achieved the plasma PK/pharmacodynamic (PD) target of % f T>MIC of at least 30% for an MIC of 4 µg/mL. Differences in weight-normalized CL were more pronounced for TAZ in CF and non-CF subjects (mean [SD]: 0.73 [0.25], 0.42 [0.13] L/hours/kg, respectively). However, the half-life was similar in CF and non-CF subjects (mean [SD]: 0.99 [0.15] hours, 1.08 [0.15] hours, respectively), suggesting that differences are unlikely to be clinically meaningful. At the recommended dose being advanced into Phase 2, subjects are projected to achieve the TAZ plasma PK/PD target of % f T>threshold concentration (Ct) of >20% for a Ct of 1 µg/mL. Conclusion: Preliminary exploratory analysis of TOL/TAZ PK in a small group of pediatric patients supports evaluation of the same TOL/TAZ dose in children with and without CF in future clinical studies. Disclosures: K. Larson, Merck: Employee, Salary. S. Yang, Merck: Employee, Salary.; B. Yu, Merck: Employee, Salary. M. G. Johnson, Merck: Employee, Salary. M. Rizk, Merck: Employee, Salary. E. Rhee, Merck: Employee, Salary.